Modulation of Tamoxifen Cytotoxicity by Caffeic Acid Phenethyl Ester in MCF-7 Breast Cancer Cells - Motawi, Tarek K. (Oxid Med Cell Longev, 2016)
Although Tamoxifen (TAM) is one of the most widely used drugs in managing breast cancer, many women still relapse after long-term therapy. Caffeic acid phenethyl ester (CAPE) is a polyphenolic compound present in many medicinal plants and in propolis. The present study examined the effect of CAPE on TAM cytotoxicity in MCF-7 cells. MCF-7 cells were treated with different concentrations of TAM and/or CAPE for 48 h. This novel combination exerted synergistic cytotoxic effects against MCF-7 cells via induction of apoptotic machinery with activation of caspases and DNA fragmentation, along with downregulation of Bcl-2 and Beclin 1 expression levels. However, the mammalian microtubule-associated protein light chain LC 3-II level was unchanged. Vascular endothelial growth factor level was also decreased, whereas levels of glutathione and nitric oxide were increased. In conclusion, CAPE augmented TAM cytotoxicity via multiple mechanisms, providing a novel therapeutic approach for breast cancer treatment that can overcome resistance and lower toxicity. This effect provides a rationale for further investigation of this combination.